1989
DOI: 10.1111/j.1365-3083.1989.tb01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone‐Reversible Monocyte Dysfunction in Patients with Chronic Fatigue Syndrome

Abstract: We studied monocyte function in 35 consecutive patients with chronic fatigue syndrome (CFS) and 25 healthy controls. Eighty-five per cent of the patients showed monocyte dysfunction characterized by marked reduction in the number of monocytes displaying immunoreactive cytoskeletal vimentin filaments, a low phagocytosis index, and a reduced expression of HLA-DR antigens. These values increased dramatically after incubation of the patients' monocytes with the opioid antagonist naloxone. Other immunological abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The existence of a state akin to endotoxin tolerance could also potentially explain a considerable body of data indicating the presence of exhausted or anergic CD4 and CD8 cells in CFS patients (Brenu et al 2011, 2016; Klimas et al 1990; Loebel et al 2014; Prieto et al 1989; Straus et al 1993). This is also true of elevated Foxp3 + Tregs which appear to have been universally reported by researchers using advanced flow cytometry techniques (Brenu et al 2011, 2014b; Curriu et al 2013; Ramos et al 2016).…”
Section: Can Immune and Metabolic Abnormalities Be Explained By Endotmentioning
confidence: 99%
“…The existence of a state akin to endotoxin tolerance could also potentially explain a considerable body of data indicating the presence of exhausted or anergic CD4 and CD8 cells in CFS patients (Brenu et al 2011, 2016; Klimas et al 1990; Loebel et al 2014; Prieto et al 1989; Straus et al 1993). This is also true of elevated Foxp3 + Tregs which appear to have been universally reported by researchers using advanced flow cytometry techniques (Brenu et al 2011, 2014b; Curriu et al 2013; Ramos et al 2016).…”
Section: Can Immune and Metabolic Abnormalities Be Explained By Endotmentioning
confidence: 99%
“…While one group reported decreases in delayed hypersensitivity skin reaction to injection of common antigens (38), two others did not (40,61). Of those studies evaluating in vitro peripheral blood mononuclear cell (indicated below by an asterisk) or T-cell function in response to various lymphocyte stimulants, five showed decreases (10,26,38,57,63), one showed increases (24), and seven showed no differences (2, 10,* 16,* 18, 40, 41, 59). The reader should note that one group reported increases in some variables, decreases in others, and no change in yet others (10); moreover, one group reported no significant differences between patients and controls when phytohemagglutinin, concanavalin A, or poke weed antigen were the stimulants but did find significantly lower activity in CFS patients when soluble antigens such as tetanus toxoid were used (16).…”
Section: Inconsistent Immune Markersmentioning
confidence: 99%
“…A number of immunological abnormalities have been described in CFS [5,13. 14,[17][18][19][21][22][23]27,28]. The data have been rather conflicting.…”
mentioning
confidence: 99%